Exchange rate misalignment, state fragility, and economic growth in sub-Saharan Africa - Brian Tavonga Mazorodze (Cogent Economics & Finance, 2021)
The sluggish and sometimes negative growth in sub-Saharan Africa has defined the objectives of most studies seeking to explain the sources of its slow growth. I contribute to this inquiry by estimating how state fragility influences the effect of exchange rate misalignment on economic growth. Since exchange rate misalignment captures the distortionary effects of inappropriate macroeconomic policies in the main, my hypothesis is that resilient and less fragile states cope better with macroeconomic imbalances making misaligned exchange rates less likely to have serious effects on growth in such countries. In testing this hypothesis, I first measure misalignment as deviations of the actual exchange rate from an estimated equilibrium level using the dynamic ordinary least squares method. I then insert this variable and its interaction with state fragility in a growth specification. In line with my hypothesis, results from the system generalised method of moments and data on 13 sub-Saharan countries observed between 2009 and 2018 show a significantly negative effect of exchange rate misalignment on growth that increases with state fragility. Based on this evidence, I urge countries in this region to improve state resilience as an effort to reduce the negative effect of exchange rate misalignment on economic growth.
Keywords: 330; economic growth; Exchange rate misalignment; state fragility; sub-Saharan Africa